EFFECTS OF PROCESSING ON THE PROXIMATE AND MINERAL COMPOSITION OF CULTURED AND CAPTURED CLARIAS GARIEPPINUS - Oyekanmi, Funmilayo Bosede; Ekundare, Olugbemi Victor; Oyekanmi, Oluwatomisin Adediji (FUDMA Journal of Sciences, 2024)
Fish and fish products serve as vital protein sources in Africa and the world in general. Since fish is typically processed before consumption, this study investigated how different processing methods affect the proximate and mineral composition of both cultured and captured Clarias gariepinus. The processing techniques employed in this research included smoking, boiling, and oven drying. Cultured catfish were sourced from Oris Farm in Osogbo, Osun State, Nigeria, while captured catfish were obtained from Asejire Dam in Oyo State. The proximate and mineral compositions of fresh, boiled, smoked, and oven-dried samples of both cultured and captured Clarias gariepinus were analyzed in triplicate. The results indicated significant differences (P<0.05) in crude protein, dry matter, moisture, ash, fiber, potassium, and phosphorus content among the different processing methods for both cultured and captured catfish samples. Potassium and phosphorus levels also varied significantly (P<0.05) across the processing methods. Boiled and oven-dried samples of both cultured and captured catfish exhibited higher crude protein and lipid content, suggesting that these processing methods provide consumers with a rich source of protein and essential nutrients. The study concludes that boiling and oven drying with samples possessing highest percentages of protein are the most effective processing methods for preparing Clarias gariepinus, ensuring optimal nutrient retention for consumers.